Missing Grace : a Kit mystery - Jones, Elizabeth McDavid, 1958- (American Girl, 2010)
In the summer of 1935, twelve-year-old Kit Kittredge's dog Grace mysteriously vanishes and Kit tries to figure out who took her and why. Includes information about pets and dog shows during the Great Depression.